2021
DOI: 10.3390/pharmaceutics13081176
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Photodynamic Therapy with Different Lights and Combined or Uncombined with Chlorhexidine on Candida spp.

Abstract: Candidiasis is very common and complicated to treat in some cases due to increased resistance to antifungals. Antimicrobial photodynamic therapy (aPDT) is a promising alternative treatment. It is based on the principle that light of a specific wavelength activates a photosensitizer molecule resulting in the generation of reactive oxygen species that are able to kill pathogens. The aim here is the in vitro photoinactivation of three strains of Candida spp., Candida albicans ATCC 10231, Candida parapsilosis ATCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In different types of infections, it has been shown that photodynamic therapy is strain- and photosensitizer-dependent [ 56 ] and that it has a cumulative effect with the mixture of other antimicrobials [ 57 ]. A factor that must be taken into account and that can increase the antimicrobial activity of the photosensitizer is the incubation/pre-irradiation time, since this could increase the joint effect of the MB + LED [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In different types of infections, it has been shown that photodynamic therapy is strain- and photosensitizer-dependent [ 56 ] and that it has a cumulative effect with the mixture of other antimicrobials [ 57 ]. A factor that must be taken into account and that can increase the antimicrobial activity of the photosensitizer is the incubation/pre-irradiation time, since this could increase the joint effect of the MB + LED [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chlorhexidine exhibits biocidal activity against Gram-positive bacteria, and, if the minimum inhibitory concentration (MIC) is maintained, it can also inhibit Gram-negative bacteria. Additionally, chlorhexidine remains active against DNA and RNA viruses and yeast, including Candida albicans [48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these medications have a limited range of action, and they can be toxic ( Morio et al, 2017 ; Rodríguez-Cerdeira et al, 2021 ). Thus, other therapeutic approaches have been investigated against oral fungal infections in recent years, e.g., using oregano oil, tea tree oil, ozone therapy, nanoparticles, and light therapy ( Ninomiya et al, 2013 ; Szweda et al, 2015 ; Maciel et al, 2016 ; Bhat et al, 2018 ; Monzillo et al, 2020 ; Pérez-Laguna et al, 2021 ). Many studies have introduced aPDT as a promising approach instead of the conventional antifungal treatments in managing oral candidiasis and denture stomatitis ( Kato et al, 2013 ; Azizi et al, 2016 ; Janeth Rimachi Hidalgo et al, 2019 ; Alves et al, 2020 ).…”
Section: Applications Of Apdt In the Treatment Of Oral Fungal Infectionsmentioning
confidence: 99%